Global Asthma Network Phase I study in Mexico: prevalence of asthma symptoms, risk factors and altitude associations—a cross-sectional study. Issue 1 (2nd December 2020) - Del-Río-Navarro, Blanca Estela; Berber, Arturo; Reyes-Noriega, Nayely; Navarrete-Rodríguez, Elsy Maureen; García-Almaraz, Roberto; Ellwood, Philippa; Garcia-Marcos, Luis; Saucedo-Ramírez, Omar Josué; Mérida-Palacio, Valente Juan; Ramos-García, Beatriz Del Carmen; Escalante-Domínguez, Alberto José; Linares-Zapién, Francisco Javier; et al.
Abstract : Background: Global Asthma Network (GAN) was established in 2012 as a development to the International Study of Asthma and Allergies in Childhood to improve asthma care globally. Objective: To survey asthma, allergic rhinitis and atopic dermatitis in primary and secondary school children and to investigate and evaluate its prevalence, severity, management and risk factors in Mexico. Methods: GAN Phase I is a cross-sectional, multicentre survey carried out in 15 centres corresponding to 14 Mexican cities throughout 2016–2019 using the validated Spanish language version of the GAN Phase I questionnaires. The questionnaires were completed by parents of 6–7-year-old primary school pupils (school children) and by 13–14-year-old adolescents. Results: A total of 35 780 school children and 41 399 adolescents participated. Wheezing ever prevalence was 26.2% (95% CI 25.8% to 26.7%) in school children and 23.9% (95% CI 23.4% to 24.3%) in adolescents. The corresponding frequencies for current wheeze were 10.2% (95% CI 9.9% to 10.5%) and 11.6% (95% CI 11.2% to 11.9%). In school children, the risk factors for current wheeze were rhinitis (OR 4.484; 95% CI 3.915% to 5.134%) and rash symptoms (OR 1.735; 95% CI 1.461% to 2.059%). For adolescents, rhinitis symptoms (OR 3.492; 95% CI 3.188% to 3.825%) and allergic rhinitis diagnosis (OR 2.144; 95% CI 1.787% to 2.572%) were the most significant. For both groups, there was a negative relation with centres' sea level altitude higher than 1500 m above mean sea level (p<0.005). Conclusions: The most important risk factors for asthma symptoms in both age groups were the presence of rhinitis and rash symptoms or diagnosis. On the other hand, sea level altitude higher than 1500 metres was a protective factor.